Blood Flow Assessment of Arteriovenous Malformations Using Intraoperative Indocyanine Green Videoangiography - Naoki Kato; Vincent Prinz; Julius Dengler; Peter Vajkoczy (Stroke Research and Treatment)
Intraoperative indocyanine green (ICG) videoangiography is widely used in patients undergoing neurosurgery. FLOW800 is a recently developed analytical tool for ICG videoangiography to assess semi-quantitative flow dynamics; however, its efficacy is unknown. In this study, we evaluated its functionality in the assessment of flow dynamics of arteriovenous malformation (AVM) through ICG videoangiography under clinical settings. ICG videoangiography was performed in the exposed AVM in eight patients undergoing surgery. FLOW800 analysis was applied directly, and gray-scale and color-coded maps of the surgical field were obtained. After surgery, a region of interest was placed on the individual vessels to obtain time-intensity curves. Parameters of flow dynamics, including the maximum intensity, transit time, and cerebral blood flow index, were calculated using the curves. The color-coded maps provided high-resolution images; however, reconstruction of colored images was restricted by the depth, approach angle, and brain swelling. Semi-quantitative parameters were similar among the feeders, niduses, and drainers. However, a higher cerebral blood flow index was observed in the feeders of large AVM (>3 cm) than in those of small AVM (P < 0.05). Similarly, the cerebral blood flow index values were positively correlated with the nidus volume (P < 0.01). FLOW800 enabled visualization of the AVM structure and safer resection, except in case of deep-seated AVM. Moreover, semi-quantitative values in the individual vessels through using ICG intensity diagram showed different patterns according to size of the AVM. ICG videoangiography showed good performance in evaluating flow dynamics of the AVM in patients undergoing surgery.